2021
DOI: 10.14309/ajg.0000000000001196
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Central Obesity on Esophageal Epithelial Barrier Function

Abstract: INTRODUCTION: We assessed if obesity perturbs the esophageal epithelial barrier function independent of promotion of gastroesophageal reflux (GER). METHODS: Thirty-eight participants were divided into 4 groups: Obesity−/GER–, Obesity+/GER−, Obesity−/GER+, and Obesity+/GER+. Esophageal intercellular space and desmosome density (structural integrity) and fluorescein leak (functional integrity) were measured. RESULTS: … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
7
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 15 publications
1
7
0
Order By: Relevance
“…Moreover, the esophageal intercellular space widths and desmosome densities of the obese patients with normal acid reflux did not differ significantly from those of patients with abnormal acid reflux, both obese and nonobese, suggesting that the esophageal barrier defects associated with visceral obesity alone are similar in severity to those associated with GERD. Using confocal laser endomicroscopy, the investigators found similar significant degrees of fluid leakage from esophageal epithelial capillaries for the obese patients without reflux and both groups of reflux patients, but not for the non-obese patients without reflux (50). These findings demonstrate that visceral obesity, independent of reflux, is associated with reduced cell adhesion proteins, dilation of intracellular spaces, and impaired esophageal mucosal barrier integrity.…”
Section: Visceral Obesity Inflammatory Cytokines and Esophageal Barrier Functionmentioning
confidence: 89%
See 2 more Smart Citations
“…Moreover, the esophageal intercellular space widths and desmosome densities of the obese patients with normal acid reflux did not differ significantly from those of patients with abnormal acid reflux, both obese and nonobese, suggesting that the esophageal barrier defects associated with visceral obesity alone are similar in severity to those associated with GERD. Using confocal laser endomicroscopy, the investigators found similar significant degrees of fluid leakage from esophageal epithelial capillaries for the obese patients without reflux and both groups of reflux patients, but not for the non-obese patients without reflux (50). These findings demonstrate that visceral obesity, independent of reflux, is associated with reduced cell adhesion proteins, dilation of intracellular spaces, and impaired esophageal mucosal barrier integrity.…”
Section: Visceral Obesity Inflammatory Cytokines and Esophageal Barrier Functionmentioning
confidence: 89%
“…TEM studies performed on esophageal biopsies from the four patient groups described by Blevins et al measured intercellular space width and desmosome density for cells of the stratum basalis (49,50). Compared with nonobese patients with normal acid reflux, the patients with visceral obesity and normal acid reflux had significantly wider mean intercellular spaces and significantly lower desmosome densities (50).…”
Section: Visceral Obesity Inflammatory Cytokines and Esophageal Barrier Functionmentioning
confidence: 99%
See 1 more Smart Citation
“…Visceral adipose tissue produces pro-inflammatory cytokines such as interleukin-1, interleukin-6, and tumor necrosis factor and adipokines such as leptin (which increases in obesity) and adiponectin (which decreases in obesity) [24][25][26]. Recent studies have suggested that visceral obesity, independent of reflux, is associated with dilatation of intracellular spaces and impaired esophageal mucosal barrier integrity [27,28]. Furthermore, these cytokines released from visceral fat may influence metaplasia of the esophagus, which affects carcinogenesis [29,30].…”
Section: Discussionmentioning
confidence: 99%
“…Obesity is also an important condition in this group. Obesity impairs the structural and functional integrity of the oesophageal barrier, leading to oesophageal injury ( 169 ). A high-calorie and fat-enriched diet affects gut permeability and TJ restructuring in the mouse model ( 170 ).…”
Section: Diseases Associated With Epithelial Barrier Impairmentmentioning
confidence: 99%